Legal Force of Peace Deed What Notaries Do in Resolution of Land Disputes in NTB Province - Sutrisno, Lalu Budi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The term written peace is regulated in Article 1851 of the Civil Code. In practice, peace agreements in the settlement of land disputes are usually caused by unlawful acts of one party that can harm a person's civil rights. This dispute can be resolved through litigation or non-litigation. In reality, non-litigation settlements before a notary are made after a court decision, so that the legal certainty of the deed becomes multi-interpretable for most people. The purpose of this writing is to analyze a peace deed that is made authentically as evidence of peace in court and to analyze the legal force of a notarial peace deed in an effort to resolve land disputes. This research is based on normative juridical legal research.Normative legal research is research that is conducted by examining theoretical approaches, concepts, and reviewing laws and regulations related to the research..Data analysis methodsdescriptive-qualitative by examining the regulations governing the power of notarial peace deeds. Data collection methods include interviews, document studies or library materials. The data analysis method used is the qualitative analysis of the Miles and Huberman model. The author's findings are that non-litigation peace can be made authentically before a notary so that it has perfect evidentiary power or its truth cannot be denied when proven in court. However, peace based on a notarial deed only has binding power and evidentiary power. Non-litigation dispute resolution can be done through negotiation, mediation, conciliation and arbitration. Meanwhile, a peace deed based on a court decision has binding legal force (permanent legal force), evidentiary power and executorial power.